A facile method for the preparation of a high-performance, hybrid separator for use in lithium-ion batteries. Issue 21 (November 2021) - Wong, Pok Yin; Zhu, Chunhong; Wang, Qianyu; Shi, Jian; Hyodo, Kenji; Kim, Ick Soo
Polyethylene (PE) membrane has poor wettability and poor thermal stability, which results in insufficient wetting by liquid electrolytes, thermal shrinkage, and no guarantee of safety. In addition, polyethylene terephthalate (PET) nonwoven fabric has inhomogeneous pores and no shutdown function. Therefore, it may cause some problems for independent use, either in the assembly or in usage. In this study, a hybrid separator used in lithium-ion batteries was investigated. The separator was fabricated by laminating a PE membrane and PET nonwoven fabric with or without a ceramic coating on the PET nonwoven. The morphology, wettability, thermal stability, and battery performance were evaluated, and the results showed that the homogeneous distribution of pores can be obtained from the hybrid separators. The wettability properties were also improved in terms of contact angle, liquid electrolyte absorption height, and the decrease in the spreading area. Moreover, with laminated PET nonwoven fabric, the hybrid separators kept the dimensional shape at 180°C for 1 hour of heating, but the PE membrane shrank and became a small wad. The difference between the shutdown and meltdown temperatures ensured that the battery was safe to use. In addition, the evaluation of the battery's performance indicated that the hybrid separators can be used instead of a PE membrane. This study showed a facile method for the preparation of a hybrid composite separator with improved wettability, thermal stability, and safety for lithium-ion batteries, and it has the potential to be used extensively in the future.